Pengaruh Faktor Psikologis dan Pribadi Terhadap Keputusan Pembelian ke Pasar Banyuasri Buleleng Setelah Revitalisasi - Maharani, Komang Indah; Indrayani, Luh (Jurnal Pendidikan Ekonomi Undiksha, 2024)
The purpose of this study is to determine the influence of psychological and personal factors, partially and simultaneously, on consumer purchase decisions. The type of money research used is causal quantitative research. The sampling technique used is non-probability sampling; the sample of this study is consumers who have shopped at Banyuasri Market, Buleleng Regency, with a sample of 100 people. The data collection method uses a questionnaire that is analyzed. The results showed that (1) there was a positive and significant influence of psychological factors on partial purchase decisions, with a significance value of <0.001 < 0.05. (2) There was a positive and significant influence of personal factors on the purchase decision, partially, with a significance value of < 0.001 < 0.05. (3) There was a positive and significant influence between psychological and personal factors on purchase decisions simultaneously, with a significance value of < 0.001 < 0.05.